Can effective pedagogy be ensured in minimally invasive surgery e-learning?. Issue 2 (1st February 2022) - Oropesa, Ignacio; Gutiérrez, David; Chmarra, Magdalena K.; Sánchez-Peralta, Luisa F.; Våpenstad, Cecilie; Sánchez-González, Patricia; Pagador, José B.; González-Segura, Ana; Langø, Thomas; Sánchez-Margallo, Francisco M.; Dankelman, Jenny; Gómez, Enrique J.
Abstract: Introduction: Effectiveness of e-learning diminishes without the support of a pedagogical model to guide its use. In minimally invasive surgery (MIS), this has been reported as a limitation when technology is used to deliver contents without a sound pedagogical background. Material and methods: We describe how a generic pedagogical model, the 3D pedagogy framework, can be used for setting learning outcomes and activities in e-learning platforms focused on MIS cognitive skills. A demonstrator course on Nissen fundoplication was developed following the model step-by-step in the MISTELA learning platform. Course design was informed by Kolb's Experiential learning model. Content validation was performed by 13 MIS experts. Results: Ten experts agreed on the suitability of content structuring done according to the pedagogical model. All experts agreed that the course provides means to assess the intended learning outcomes. Conclusions: This work showcases how a general-purpose e-learning framework can be accommodated to the needs of MIS training without limiting the course designers' pedagogical approach. Key advances for its success include: (1) proving the validity of the model in the wider scope of MIS skills and (2) raising awareness amongst stakeholders on the need of developing training plans with explicit, rather than assumed, pedagogical foundations. Abbreviations: MIS: minimally invasive surgery; TEL: technology enhanced learning